A Systematic Review of Dietary Supplements and Alternative Therapies for Weight Loss. Issue 7 (23rd June 2021) - Batsis, John A.; Apolzan, John W.; Bagley, Pamela J.; Blunt, Heather B.; Divan, Vidita; Gill, Sonia; Golden, Angela; Gundumraj, Shalini; Heymsfield, Steven B.; Kahan, Scott; Kopatsis, Katherine; Port, Ava; et al.
Abstract : Objective: Dietary supplements and alternative therapies are commercialized as a panacea for obesity/weight gain as a result of the minimal regulatory requirements in demonstrating efficacy. These products may indirectly undermine the value of guideline‐driven obesity treatments. Included in this study is a systematic review of the literature of purported dietary supplements and alternative therapies for weight loss. Methods: A systematic review was conducted to evaluate the efficacy of dietary supplements and alternative therapies for weight loss in participants aged ≥18 years. Searches of Medline (PubMed), Cochrane Library, Web of Science, CINAHL, and Embase (Ovid) were conducted. Risk of bias and results were summarized qualitatively. Results: Of the 20, 504 citations retrieved in the database search, 1, 743 full‐text articles were reviewed, 315 of which were randomized controlled trials evaluating the efficacy of 14 purported dietary supplements, therapies, or a combination thereof. Risk of bias and sufficiency of data varied widely. Few studies ( n = 52 [16.5%]) were classified as low risk and sufficient to support efficacy. Of these, only 16 (31%) noted significant pre/post intergroup differences in weight (range: 0.3‐4.93 kg). Conclusions: Dietary supplements and alternative therapies for weight loss have a limited high‐quality evidence base of efficacy. Practitioners and patients should be aware of the scientific evidence of claims before recommending use.